Wpływ transatlantyckiego dialogu edukatorów na współczesny proces edukacyjny we współpracujących ze sobą szkołach z USA i Europy - Olędzka, Monika; Oldham, Rhett (Studia Edukacyjne, 2024)
This article explores the impact of the Transatlantic Educators Dialogue (TED) Program on modern educational practices in schools across the US and Europe, analyzing survey results from participants. It highlights how global education shapes attitudes among students and educators. The TED Program aims to cultivate responsible, culturally aware global citizens through interdisciplinary learning that integrates diverse fields of knowledge. It promotes cultural, linguistic, and social competencies through international collaboration. Surveyed teachers and students report significant social and linguistic development, appreciating the chance to compare educational systems globally. Both data and testimonials underscore TED’s profound influence on international education, fostering personal growth and enhancing global citizenship.